Generation of an Attenuated Tiantan Vaccinia Virus Strain by Deletion of Multiple Genes - Li, Yiquan; Zhu, Yilong; Chen, Shuang; Li, Wenjie; Yin, Xunzhe; Li, Shanzhi; Xiao, Pengpeng; Han, Jicheng; Li, Xiao; Sun, Lili; Jin, Ningyi (Frontiers in Cellular and Infection Microbiology, 2017)
An attenuated vaccinia virus-MVTTEAB-was constructed by knocking out non-essential gene segments related to the virulence and immunomodulatory functions of the vaccinia virus Tiantan strain (VTT). The shuttle vector plasmids pTC-EGFP, pTE-EGFP, pTA35-EGFP, pTB-EGFP and pTA66-EGFP were constructed and combined with the early and late strong promoter pE/L and enhanced green fluorescent protein as an exogenous selectable marker. Then, through the homologous recombination technology and Cre/loxP system, the following gene fragments were gradually knocked out one by one: TC7LTK2L, TE3L, TA35R, TB13R and TA66R. Ultimately, the five-segment-deleted attenuated strain MVTTEAB was obtained. Knockout of these segments and genetic stability of MVTTEAB were confirmed, and it was also shown that knockout of these segments did not affect the replication ability of the virus. Further, a series of in vivo and in vitro experiments demonstrated that the virulence of MVTTEAB was weakened significantly, but at same time, high immunogenicity was maintained. These results indicate that MVTTEAB has potential for clinical use as a safe viral vector or vaccine with good attenuation and immunogenicity.